Understanding the Financial Performance of PT PLN (Persero): A Narrative on State-Owned Enterprise (SOE) with a Mandate of Electricity in Indonesia - Hendrocahyo; Lestari Kurniawati (Bina Nusantara University, 2022)
As the only electrical company that sells electric power to society and performs the assignments from the government, the financial performance of PT PLN (Persero) is attracting public attention. Some perspectives worry about PT PLN (Persero)’s financial condition and even give a negative sentiment. The research explored how to understand the financial performance of PT PLN (Persero) through a narrative constructed by data storytelling concept for neutralizing the public’s tension. The research used the stories retrieved from interviews, e-mail correspondence, and annual reports. Based on the data collected in 2020, PT PLN (Persero) has shown improvement. The company has positive income growth, an increase in assets, a decrease in liabilities, and improved financial ratios compared with last year’s performance. Even though PT PLN (Persero) gets government support, the company’s initiative program also influences financial improvement. PT PLN (Persero) also has done some mitigation actions for the risk it faced, such as paying the principal debt and its interest on time, maintaining the financial ratio, and ensuring cash availability. In addition, the monitoring from the Ministry of Finance also helps PT PLN (Persero) to maintain its financial performance safe. Lastly, the Ministry of SOE hopes that society can consider PT PLN (Persero) ’s effort to provide electricity to all Indonesian regions as part of the valuation of the company.